2006
DOI: 10.4161/psb.1.6.3563
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Allelochemicals From Roots and Root Exudates of Leafy Spurge (Euphorbia esulaL.)

Abstract: Invasive plants are a widespread problem but the mechanisms used by these plants to become invasive are often unknown. The production of phytotoxic natural products by invasive weeds is one mechanism by which these species may become successful competitors. Here, we conducted a bioactivity-driven fractionation of root extracts and exudates from the invasive plant leafy spurge (Euphorbia esula L.), and structurally characterized jatrophane diterpenes and ellagic acid derivatives. Ellagic acid derivatives and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Furthermore, the permeability of allelochemicals to root tissues was reported to be greater than that to shoot tissues (Nishida et al, 2005) due to the direct contact between the root and phytotoxic compounds present in extract. Those compounds might inhibit or reduced rate of cell division (Wang et al, 2002;Qin et al, 2006) which is highly active at meristematic tissue of the growing root tip.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the permeability of allelochemicals to root tissues was reported to be greater than that to shoot tissues (Nishida et al, 2005) due to the direct contact between the root and phytotoxic compounds present in extract. Those compounds might inhibit or reduced rate of cell division (Wang et al, 2002;Qin et al, 2006) which is highly active at meristematic tissue of the growing root tip.…”
Section: Discussionmentioning
confidence: 99%
“…Elmore & Paul (1983) reported high concentration of phenolics in E. supina and E. maculata, which is supported by previous findings of Rice (1969), who reported phenolics and gallic acid in E. supine. Wanger et al, (1970), Manners & Wong (1985), Manners (1987), Manners & Davis (1987) and Qin et al (2006) have identified several phototoxins, including relatively strong phytotoxins Kaempferol-3-glucuronide and I-hexaconsanol in aqueous extracts of the whole plant, and moderately diterpenes jatrophane in leafy spurge roots. Euphorbia esula (Evans & Kinghorn, 1977;Roberts & Olson, 1999;Zhi Qiang et al, 2008) and E. heliescopia (Jiangbo et al, 2010) contains di-and tri-terpenoids and condensed tannins.…”
Section: Allelochemicals In Euphorbia Speciesmentioning
confidence: 99%
“…Additionally, under a bioactivity driven fraction ation, EA has been isolated from the root extracts of leafy spurge (Euphorbia esula L.), an invasive plant spe cies [13]. Treatments with EA reduced the fresh weight and root elongation of Arabidopsis seedlings [13].…”
Section: Introductionmentioning
confidence: 99%